Abundance, distribution and bioaccumulation of microplastics and its potential impacts in mangrove environment / Priya Mohan - Priya , Mohan (2024)
Plastic pollution has become a global issue of transboundary contamination, necessitating comprehensive interdisciplinary research to comprehend the negative impacts. This research aims to identify the mobility of plastic bottles in the open oceans using GPS, to determine the prevalence and distribution of microplastics in mangrove sediment, water and Anadara granosa, to determine the microplastic uptake in Daphnia magna and A. granosa, and to evaluate the feasibility of valorisation plastic waste through hydrothermal liquefaction (HTL). To achieve the first objective, five tracking devices in PET bottles (B1, B2, B3, B4, and B5) were deployed in Cherating, Matang, and Kuala Selangor and their trajectory movement was monitored using a GPS system. For the second objective, sediment, water, and A. granosa were collected from Matang, Kuala Selangor, Sedili Besar, and Cherating mangroves. The sediment was collected using an auger at a depth of 1-50cm, and the microplastics in water were obtained by submerging a plankton net with a mesh size of 90μm for one hour. While A. granosa were obtained from the study sites. The microplastics from sediment, water and A. granosa were extracted using vacuum filtration and analyzed under a dissecting microscope to categorize them based on sizes, shapes, and colours, while polymer types were determined via FTIR. For the third objective, Daphnia magna and A. granosa were exposed to various shapes and sizes of PP microplastics for 96 and 264 hours, respectively. Microplastic uptake by Daphnia magna and A. granosa was observed using fluorescent and dissecting microscopes, respectively. As for the depolymerization of PP and PET (objective four), the experiment involved different alkaline concentrations and reaction times via a 2-factorial experimental design. The deployment of the tracking device revealed that B2 deployed in the Straits of Malacca travelled the longest distance of 8984 km. Conversely, the remaining B1, B3, B4 and B5 bottles beached at vegetation areas in Tittu Island (Philippines), Ao Talo Malaka (Thailand), Maldives Island and Mersing (Malaysia), respectively. Plastic beaching can cause polymer fragmentation and microplastic accumulation in the marine environment. Studies on microplastic pollution in mangroves found the highest levels in sediment (151 ± 1.91 particles/kg) during the Southwest Monsoon and in water (43400 ± 9.19 particles/m3) during the Intermonsoon. This study also found that A. granosa from Matang had the highest amount of microplastics (0.40 ± 0.2 particles/g). Overall, the dominant microplastic in the sediment, water and A. granosa were particles of <0.1mm, fragment, blue, and rayon polymer. A. granosa also accumulated microorganisms (Pseudomonas, Rhodococcus, Mycoplasma, and Candidatus thiophysa) and chlorinated organic pollutants (1-propene, 1,2,3-trichloro-, (Z)-; 1,1,2,3,3-pentachloropropane, and 1,1,1,2-tetrachloroethane) from its environment. Further laboratory investigation revealed that Daphnia magna and A. granosa preferred uptaking 0.1mm fragment particles. Microplastics pose a significant adverse impact on the marine environment and organisms. Thence, to address plastic pollution and reduce microplastic dispersion, depolymerizing PP (tetrapentacontane, 1,54-dibromo-, 1,54-dibromo-hexacontane, and acetic acid (2,4-dichlorophenyl) methyl ester) and PET (tetrapentacontane, 1,54-dibromo, and dotriacontane) produced fuel byproducts, highlighting sustainable approaches. Further research endeavours are essential to develop effective strategies for mitigating plastic pollution sustainably.